Localizing and transnationalizing contentious politics global civil society movements in the Philippines. - Tadem, Teresa S. Encamacion (Lexington Books, 2009)
The Philippines makes an interesting case for examining direct and collective acts of contention against the neoliberal project of economic globalization. Crippled by foreign debt, indiscriminate liberalization of trade, falling stock markets, and perpetual corruption, the Philippines is also a democratic polity and one of the few countries in Asia with a vibrant and dynamic civil society sector. This collection has chapters on the Freedom from Debt Coalition's campaign on debt relief, the Stop-the-New-Round Coalition's advocacy to change international trade rules and barriers, the global taxation initiative as embodied in Tobin tax advocacy in the country, the Transparency and Accountability Network's anti-corruption effort, and the Philippine Fair Trade Forum's enterprise on fair trade. Localizing and Transnationalizing Contentious Politics is the first work of its kind to focus on five global civil society movements in the Philippines and their responses to the inequities of neoliberal globalization. Northern scholars have acknowledged the persistent absence of the South in research on activism around global issues, and this book can help fill this gap. Using political process theory as a framework, the book traces the emergence, development and diffusion of these social movements in the Philippines. Globalization is taken as the environment in which they operate to highlight the role of increased interdependence and internationalization, and the predominance of a particular ideology in the dynamics of contention.